Forecasting Indonesia's Non-Oil and Gas Exports Using the Exchange Rate as an Exogenous Variable with the ARIMAX Model: Peramalan Ekspor Nonmigas Indonesia Menggunakan Variabel Eksogen Nilai Kurs Dengan Model Arimax - Ihwal, Muhammad; Laome, Lilis; Salsabilah, Adelfina; Ningtyas, Rita Ayu (UNIB Press, 2025)
This study aims to develop an ARIMAX model for forecasting Indonesia’s non-oil and gas export values for the period of March to June 2025. The variables used include Indonesia’s non-oil and gas exports (Z) and the exchange rate (X), obtained from the Ministry of Trade and Bank Indonesia. The export data is monthly time series data characterized by autocorrelation. The forecasting method employed is the Autoregressive Integrated Moving Average with Exogenous Variables (ARIMAX), which extends the ARIMA model by incorporating external predictor variables. The results show that the ARIMAX(0,1,1) model is the most suitable for forecasting, yielding a Mean Absolute Percentage Error (MAPE) of 5.01%. Using the Maximum Likelihood Estimation (MLE) method, the derived model is Ẑₜ = Zₜ₋₁ - 0.4153εₜ₋₁ - 0.00000608Xₜ. The forecast indicates that Indonesia’s non-oil and gas exports will reach USD 23,692.17 million in June, with the lowest projected value in April at USD 23,003.46 million.